Understanding capital markets volume 1 : a flow of funds financial model - Hendershott, Patric H (Lexington, Mass. : Lexington Books, 1977)
The book is a study carried out on long-term financing, modeling, and forecasting which was carried out over a three-year period 1974-1976 at the Salomon Brothers Center for the study of financial Institutions of the graduate School of Business Administration of New York University, with the support of a large grant from the American Council of Life Insurance Companies.
Includes index
Includes bibliographies footnotes.
usc 31/7/17
Loans
Keywords: Finance; Saving and investment; Flow of funds; Capital markets; United States